Multi-Omic Analyses Reveal Habitat Adaptation of Marine Cyanobacterium Synechocystis sp. PCC 7338 - Jeong, Yujin; Hong, Seong-Joo; Cho, Sang-Hyeok; Yoon, Seonghoon; Lee, Hookeun; Choi, Hyung-Kyoon; Kim, Dong-Myung; Lee, Choul-Gyun; Cho, Suhyung; Cho, Byung-Kwan (Frontiers in Microbiology, 2021)
Cyanobacteria are considered as promising microbial cell factories producing a wide array of bio-products. Among them, Synechocystis sp. PCC 7338 has the advantage of growing in seawater, rather than requiring arable land or freshwater. Nonetheless, how this marine cyanobacterium grows under the high salt stress condition remains unknown. Here, we determined its complete genome sequence with the embedded regulatory elements and analyzed the transcriptional changes in response to a high-salt environment. Complete genome sequencing revealed a 3.70 mega base pair genome and three plasmids with a total of 3,589 genes annotated. Differential RNA-seq and Term-seq data aligned to the complete genome provided genome-wide information on genetic regulatory elements, including promoters, ribosome-binding sites, 5'- and 3'-untranslated regions, and terminators. Comparison with freshwater Synechocystis species revealed Synechocystis sp. PCC 7338 genome encodes additional genes, whose functions are related to ion channels to facilitate the adaptation to high salt and high osmotic pressure. Furthermore, a ferric uptake regulator binding motif was found in regulatory regions of various genes including SigF and the genes involved in energy metabolism, suggesting the iron-regulatory network is connected to not only the iron acquisition, but also response to high salt stress and photosynthesis. In addition, the transcriptomic analysis demonstrated a cyclic electron transport through photosystem I was actively used by the strain to satisfy the demand for ATP under high-salt environment. Our comprehensive analyses provide pivotal information to elucidate the genomic functions and regulations in Synechocystis sp. PCC 7338.